Blanco DECam Bulge Survey (BDBS) IV: Metallicity distributions and bulge structure from 2.6 million red clump stars. Issue 1 (9th July 2022) - Johnson, Christian I; Rich, R Michael; Simion, Iulia T; Young, Michael D; Clarkson, William I; Pilachowski, Catherine A; Michael, Scott; Marchetti, Tommaso; Soto, Mario; Kunder, Andrea; Koch-Hansen, Andreas J; Katherina Vivas, A; et al.
ABSTRACT: We present photometric metallicity measurements for a sample of 2.6 million bulge red clump stars extracted from the Blanco DECam Bulge Survey (BDBS). Similar to previous studies, we find that the bulge exhibits a strong vertical metallicity gradient, and that at least two peaks in the metallicity distribution functions appear at b < −5°. We can discern a metal-poor ([Fe/H] ∼ −0.3) and metal-rich ([Fe/H] ∼ +0.2) abundance distribution that each show clear systematic trends with latitude, and may be best understood by changes in the bulge's star formation/enrichment processes. Both groups exhibit asymmetric tails, and as a result we argue that the proximity of a star to either peak in [Fe/H] space is not necessarily an affirmation of group membership. The metal-poor peak shifts to lower [Fe/H] values at larger distances from the plane while the metal-rich tail truncates. Close to the plane, the metal-rich tail appears broader along the minor axis than in off-axis fields. We also posit that the bulge has two metal-poor populations – one that belongs to the metal-poor tail of the low latitude and predominantly metal-rich group, and another belonging to the metal-poor group that dominates in the outer bulge. We detect the X-shape structure in fields with |Z| > 0.7 kpc and for stars with [Fe/H] > −0.5. Stars with [Fe/H] < −0.5 may form a spheroidal or 'thick bar' distribution while those with [Fe/H] −0.1 are strongly concentrated near the plane.